MENGGALI PRAKTIK LITERASI RESEPTIF ANAK USIA DINI DI RUMAH: PERSPEKTIF ORANG TUA - Fatimah Noor Isnaini; Endah Windiastuti; Untariana, Ajeng Fitri (LP2M IAIN Sultan Amai Gorontalo, 2025)
The purpose of this study is to analyze the role of parents in efforts to develop receptive literacy for early childhood in children aged 5-6 years. The method used in this research is a case study with a qualitative approach. The results of the study show that several activities that parents can do at home to improve receptive literacy skills for early childhood are using media in the form of applications and animated videos that are played on smartphones or television screens. In addition, parents can write the names of objects on objects in the house. Another medium that can be used is pasting letters and pictures on the wall to introduce various kinds of letters to children. Parents can also make siblings, namely brothers and sisters, as motivation for children to learn to read and listen. Parents’ awareness of the importance of literacy culture plays a crucial role in optimizing children’s abilities, particularly when much of their time is spent at home with their parents.